(untitled) (Ameghiniana, 2014)
Fifteen paleocommunities are recognized in a 26 m thick interval (Leoipustula fauna) from the upper section of the Hoyada Verde Formation at its type locality. The paleoecological analysis was based on Ausich’s component concept, which allows to enhance the importance of certain groups of the macrofauna and to infer the factors that limited their distribution. Taking into account that the biomass is a more adequate parameter than the numerical abundance for paleoecological reconstructions, relative abundance was expressed as a percentage of the total biovolume. Diversity values were calculated using Shannon-Weaver’s index from biovolume data. These are reliable to estima te the physiological stress conditions in the studied assemblages. The paleocommunities are grouped in three sets, each one characterized by its main component: brachiopod, bivalve and bryozoan communitieso In general, the paleoecological characteristics studied in each community indicate a stable marine environment, such as an open platform with moderate bottom currents. However, the brachiopod communities show the highest diversity values and the bryozoan communities the lowest, suggesting small changes in the physiological stress conditions associated with the bottom currents in an environment not exposed to drastic changes. In general, this interpretation is consistent with postglacial transgression models that have been proposed for the Late Paleozoic western Argentinian basins.